Yield and yield component trait analysis with DArT genotyping for GWAS in soybean grown in drought conditions of Kazakhstan - Amangeldiyeva, Aigul; Yerzhebayeva, Raushan; Mazkirat, Shynar; Didorenko, Svetlana; Bastaubayeva, Sholpan; Maikotov, Bekzhan; Kassenov, Rinat; Jenisbayeva, Assel; Shavrukov, Yuri (Frontiers in Plant Science, 2025)
Development of drought tolerant cultivars of soybean is the single best way to address the challenge of global climate change and very limited water resources for crop irrigation in Central Asia including Kazakhstan. A set of 188 soybean cultivars with diverse origins was assessed for genome-wide association study (GWAS) for yield and eight yield-related traits in both irrigated (well-watered, WW) and non-irrigated (drought) conditions during 2 years in field trials in South-Eastern Kazakhstan. The 295K Diversity array technology (DArT) analysis was applied, and 16K filtered DArT markers were used for genotyping of 183 soybean accessions. In the results, 41 quantitative trait nucleotides (QTN) were identified as significantly associated with nine studied traits. To verify these results, bulk segregant analysis (BSA) was carried out in six breeding lines originating from two crosses between high-yielding under drought cvs, Sponsor and Zen, with drought sensitive cv Lastochka. The evaluation of combined results revealed 10 most significant QTN and eight most promising putative candidate genes, which were selected and tested for their gene expression using RT-qPCR under drought compared with WW controls. Among them, glucose-6-phosphate isomerase (G6PI), pentatricopeptide repeats (PPR) protein, and ABC transporter, associated with seed yield, seed weight per plant, and plant height, were highly upregulated in drought tolerant genotypes. In contrast, two other genes, Rab-GDP dissociation inhibitor (Rab-GDI) and Transducin with WD40 repeats, associated with seed yield, showed repression in the same genotypes. These verified genes involved in the control of yield and yield-related traits can be used for marker-assisted selection to develop novel genotypes and new soybean cultivars tolerant to strong drought in Kazakhstan and in other countries with similar conditions.